Reflections on research and practice nexus through a Case Study Investigation at Phillip Island Nature Park - Sidh Sintusingha; Emma Stevens (Landscape Review)
The article reflects on a collaboration between academia and the profession to conduct a case study, funded through and framed by the US-based Landscape Architecture Foundation Case Study Investigation program (LAF CSI), on the practitioner’s project Phillip Island Nature Parks (PINP) master plan and stage 1 (new visitor centre precinct).  While benefits of such collaborations are well-known, nuanced, varying stakeholder objectives and relationships are inherent issues to negotiate in order to optmise collaborations. This include engaging with and acknowledging the client’s stewardship (PINP) of place. Such practices can leverage greater benefits that recognise and reinforce the landscape architecture disciplinary proficiency as ‘placemakers’. The role of LAF as a medium to facilitate the objectives, relationship and training is integral to successful collaboration. A good understanding of and respect for each other’s role is critical as is a constant engagement/communication throughout the process.